SOME OBSERVATIONS ON THE CULTURE OF THE AIRBREATHING FISH CHANNA STRIATA (BLOCH) IN FARM PONDS - Ravindranath, K (Indian Journal of Fisheries, 2011)
The air-breathing fish Channa striata(Bloch), commonly called the striped murrel(snake-head) is one of the most sought-afterfreshwater fishes in several parts of India.While snake-heads (Channa spp.) are culturedin cages and ponds in some of theSouth-East Asian countries